Clinical and epidemiological study of acute pelvic inflammatory disease. Arzobispo Loayza National Hospital - De la Cruz, Gina (2015)
OBJECTIVES: To study the behavior of pelvic inflammatory disease (PID) in patients treated at a state hospital. DESIGN: Descriptive, longitudinal and retrospective study MATERIALS AND METHODS: Archbishop Loayza, Department of Gynecology, for the length July 2000 to July 2003, National Hospital 68 patients were treated for PID in our center were studied. Data for the study of the review of the medical records were on file was obtained. RESULTS: The EPI represented 4.1% of total gynecological admissions. Misdiagnosis income was 15% of cases, corresponding to these 4 cases of acute appendicitis, 1 case of endometriosis, 2 cases of complicated adnexal cyst and 2 cases of ectopic pregnancy. The number of sexual partners, sexual intercourse during menstruation, history of pelvic inflammatory disease and use of IUDs for contraception were the factors most outstanding epidemiological risk; similarly, lower abdominal pain and leukocytosis were the most prominent clinical and laboratory elements. CONCLUSIONS: The most common treatment was medical therapy, the clindamycin / gentamicin scheme and a satisfactory response is observed.